Potensi Pengolahan Limbah Bahan Berbahaya dan Beracun di Industri Semen - Andini Siti Rohmana; Gina Lova Sari (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Cement production has the potential to increase greenhouse gas (GHG) emissions, particularly carbon dioxide (CO2) emissions. The cause of CO2 produced by the cement industry is reported to come from two sources, namely the combustion process in the kiln and the calcination process in the clinker making process. The large amount of CO2 gas produced in the production process puts pressure on every cement industry to try to find alternative fuels and raw materials to maintain or reduce CO2 emissions. One of the alternative raw materials that can be used as a source of fuel and alternative raw materials is hazardous and toxic waste with certain criteria. This study is an observational study, in which the cement production process and waste management in one of the cement industries are observed to obtain primary data in the form of the types of waste used. Internal waste is used as a substitute for raw materials and fuel substitutes. The process of waste utilisation in the cement industry is carried out by co-processing. The process of waste utilisation requires control, so each activity must be monitored. The results show that the cement products resulting from the process of using waste as a raw material substitute are of good quality and meet the criteria contained in the Annex to Ministerial Regulation No. 6 of 2021.